2006
DOI: 10.1118/1.2181291
|View full text |Cite
|
Sign up to set email alerts
|

A bench‐top megavoltage fan‐beam CT using ‐photodiode detectors. II. Image performance evaluation

Abstract: Megavoltage computed tomography (MVCT) is a potential imaging tool for positioning and dose delivery verification during image guided radiotherapy. The problem with many MVCT detectors, however, is their low detective quantum efficiency (DQE) which leads to poor low contrast resolution (LCR) and high image noise. This makes separating the tumors from the soft tissue background difficult. This manuscript describes the imaging performance of our bench-top MVCT scanner that uses an 80-element detector array consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…1,2 The wide-gap semiconductors magnesium, zinc, and cadmium tungstate (MgWO 4 , ZnWO 4 , CdWO 4 ) are remarkable members of this family of compounds and their properties have been extensively studied during the past decade. In particular, their scintillating efficiency and radiation hardness make them prototypic scintillators for rare-event searches.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The wide-gap semiconductors magnesium, zinc, and cadmium tungstate (MgWO 4 , ZnWO 4 , CdWO 4 ) are remarkable members of this family of compounds and their properties have been extensively studied during the past decade. In particular, their scintillating efficiency and radiation hardness make them prototypic scintillators for rare-event searches.…”
Section: Introductionmentioning
confidence: 99%
“…23 For indirect detection, some of the detectors considered include thick optical fibers detecting Cerenkov radiation, 24 2D polymer matrices filled with Gd 2 O 2 S : Tb phosphor, 25 as well as 1D and 2D crystalline scintillators ͑e.g., CsI:Tl, Bi 4 Ge 3 O 12 , CdWO 4 , and ZnWO 4 ͒, employing the concept of segmentation. [26][27][28][29][30][31][32][33][34] A series of theoretical and empirical studies has been previously reported on 2D segmented crystalline scintillators, which consists of matrices of scintillating crystals separated by septal walls to limit the lateral spread of optical photons. 25,[35][36][37][38][39][40] Monte Carlo simulations of radiation and optical transport have suggested that EPIDs employing segmented CsI:Tl and Bi 4 Ge 3 O 12 ͑BGO͒ detectors up to 40 mm thick can offer DQE values of up to 29% and 42%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These detectors are based on concepts involving high pressure gas ͑e.g., xenon͒ chambers employing tungsten walls, [10][11][12] thick optical fibers detecting Cerenkov radiation, 13 thick HgI 2 photoconductors, 14 segmented phosphors based on photopolymer matrices, 15 and segmented crystalline scintillators which consist of 2D matrices ͑or 1D arrays͒ of scintillator crystals separated by optically opaque septal walls. 7,[16][17][18][19] Among these approaches, segmented crystalline scintillators offer significantly improved QE, with only limited loss in spatial resolution, and possibly no substantial increase in noise compared to conventional AMFPIs. In order to examine this strategy, 1D segmented arrays incorporating zinc tungstate ͑ZnWO 4 ͒ and cadmium tungstate ͑CdWO 4 ͒ scintillators, [17][18][19] as well as 2D segmented matrices employing bismuth germanate ͑BGO͒, thallium-doped cesium iodide ͑CsI:Tl͒ and CdWO 4 scintillators, 7,[20][21][22] have been investigated by different research groups.…”
Section: Introductionmentioning
confidence: 99%
“…7,[16][17][18][19] Among these approaches, segmented crystalline scintillators offer significantly improved QE, with only limited loss in spatial resolution, and possibly no substantial increase in noise compared to conventional AMFPIs. In order to examine this strategy, 1D segmented arrays incorporating zinc tungstate ͑ZnWO 4 ͒ and cadmium tungstate ͑CdWO 4 ͒ scintillators, [17][18][19] as well as 2D segmented matrices employing bismuth germanate ͑BGO͒, thallium-doped cesium iodide ͑CsI:Tl͒ and CdWO 4 scintillators, 7,[20][21][22] have been investigated by different research groups. Recently, a 40 mm thick segmented CsI:Tl detector, with an element-toelement pitch of 1.016 mm and an area of 16.25 ϫ 16.25 cm 2 , has been developed and evaluated by our group.…”
Section: Introductionmentioning
confidence: 99%